A new species of Brachylepis Kolbe, 1894 from Tanzania (Scarabaeidae: Melolonthinae: Leucopholini) - Sehnal, Richard (Zootaxa, 2018)
The Afrotropical genus Brachylepis Kolbe, 1894 (Scarabaeidae: Melolonthinae: Leucopholini) was established for Coniopholis elephas Gerstaecker, 1867 from Kenya. Subsequently, Brenske (1898) described Brachylepis bennigseni from Tanzania (Pare Mountains), and Lacroix (2009) described B. werneri from Ethiopia (Negele Borana) and synonymised B. bennigseni with B. elephas. Thus, the genus contains only two species. From the closely related Afrotropical leucopholine genera (e.g., Eulepida Kolbe, 1894, Eulepidopsis Burgeon, 1946, Cochliotis Kolbe, 1894) it differs in having nine antennomeres, the terminal maxillary palpomere expanded near midlength, and an incomplete metatibial carina (Lacroix 2009, 2010).